The use of navigation systems in naturalistic driving. (2nd April 2016) - Knapper, Allert; Nes, Nicole Van; Christoph, Michiel; Hagenzieker, Marjan; Brookhuis, Karel
Abstract: Objective: In this study, we assessed the use of portable navigation systems in everyday driving by applying in-vehicle naturalistic driving. Method: Experienced users of navigation systems, 7 females and 14 males, were provided with a specially equipped vehicle for approximately 1 month. Their trips were recorded using 4 cameras, Global Positioning System (GPS) data, and other sensor data. The drivers' navigation system use data were coded from the video recordings, which showed how often and for how long the system was activated and how often and for how long a driver operated the system. Results: The system was activated for 23% of trips, predominantly on longer and unique trips. Analyses of the percentage of time for which the speed limit was exceeded showed no evidence of differences between trips for which the navigation system was used or not used. On trips for which the navigation system was activated, participants spent about 5% of trip time interacting with the device. About 40% of interacting behavior took place in the first 10% of the trip time, and about 35% took place while the car was standing still or moving at a very low speed; that is, 0–10 km/h. Conclusion: These results shed light on how and when drivers use navigation systems. They suggest that although drivers regulate their use of such systems to some extent, they often perform risky tasks while driving.